PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BINTANG LIMA IMADA - Melani, Suci; Wasiman (LPPM Universitas Putera Batam, 2022)
The company PT Bintang Lima Imada is a company engaged in the distribution of basic necessities. The company, PT Bintang Lima Imada, is located in the Citra Buana Center complex Blok e No. 8 Seraya Batam, Lubuk Baja District, Batam city. The company sells food products such as flag milk, syrup, bread and vitamins. The company has subsidiaries located in Tanjung Balai Karimun and Tanjung Pinang. A good company certainly has a good performance. In terms of employee performance, employees at PT Bintang Lima Imada have less than optimal performance because the company has not been able to achieve the set targets in the last six months. This is because leaders who pay less attention to the company's achievement so that the problem of achieving company targets is not optimal every month. At PT Bintang Lima Imada, there are employees whose work discipline is still lacking due to frequent delays and absenteeism at work, resulting in a lot of work being delayed. The population taken by the researchers were all employees at PT Bintang Lima Imada totaling 115 employees. The sample was selected through existing techniques, in this study using a saturated sample technique which means using all existing population sets. The sample in this study consisted of 115 respondents. The results show that there is a simultaneous and partial influence between leadership and work discipline variables on employee performance.